Pembelajaran Berbasis Budaya Meningkatkan Hasil Belajar Kognitif Siswa SMA di Kota Denpasar - I Made Surya Hermawan; Hadi Suwono; Herawati Susilo; Desak Nyoman Budiningsih (Universitas Muhammadiyah Prof. Dr. Hamka, 2020)
Background: One of the learning objectives is to develop a cognitive process dimension seen in cognitive learning outcomes. In fact, this has not been implemented optimally in the learning process. The Balinese culture-based biology learning model is seen as an alternative to developing the cognitive process dimension. This study aims to reveal the effect of the Balinese culture-based biology learning model through the cognitive learning outcomes of high school students in Denpasar City. Methods: This study was conducted using a non-equivalent pretest-posttest control group design. The research subjects were 144 students who were taken using cluster random sampling technique. The data collection instrument was in the form of multiple choices questions which were categorized into questions of lower-order thinking skills (LOTS) and questions of higher-order thinking skills (HOTS). Results: The results of data analysis showed that: 1) there was a significant difference in cognitive learning outcomes between the experimental class and the control class (p <0.05); 2) the Balinese culture-based biology learning model increased students' cognitive learning outcomes by 18.21%; 3) the Balinese culture-based biology learning model improves lower-order thinking skills (LOTS) by 8.44% and higher-order thinking skills (HOTS) by 17.92%. Conclusions: This study concludes that the Balinese culture-based biology learning model improves cognitive learning outcomes and has the potential to develop higher-order thinking skills of high school students in Denpasar City.